Effect of Urea Treated Rice Straw in Combination with Fermented Ground Samanea Saman Pods on Quality of Rice Straw and a Reduction of Afl atoxin B1 (AFB1) Level Using In vitro Gas Production Technique - พวงชมภู, อรอนงค์; แมนสถิต, จุฬาสินี; อุ่นสำโรง, มิ่งขวัญ; ศรีริโม้, สุรีรัตน์; ขาวทอง, ชัยณรงค์; ปานประเสริฐ, พิลาสลักษณ์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This experiment aims to determine the effect of enhancement quality of rice straw contaminated with afl atoxin B1 (AFB1) by treated with urea and ground Samanea saman pods fermented (GSSF) on rumen degradability using in vitro gas technique. The results showed that when fermented ground Samanea saman pods with lactic acid bacteria from yogurt drink, 0, 3, 5, 7 and 14 days, the number of total bacteria by microscopic count increased over the period of fermentation (P < 0.05). The dry matter content as in the range 48 - 49 % (P > 0.05) and protein were increased by the number of days fermentation (P < 0.05). The amount of aflatoxin (ppb) after fermented rice straw with 5 % GSSF only was decreased with the number of days of fermentation (P < 0.05). The crude protein content in rice straw fermented with 2.5 % urea and 2.5 % GSSF of 5 and 7 days of fermentation were higher than 5 % GSSF (P < 0.05). The rumen degradability in beef cattle using in vitro gas technique of rice straw fermented with 2.5 % urea and 2.5 % GSSF were higher than fermented with 5 % GSSF (P < 0.05). The amount of afl atoxin (ppb) in rumen fluid after incubation at 0, 5, 16 and 24 h decreased with increasing incubation time (P < 0.05) and variability reduction of Aflatoxin in treatment when the incubation time increases.